Risk of Complications After THA Increases Among Patients Who Are Coinfected With HIV and Hepatitis C. Issue 2 (February 2018) - Mahure, Siddharth A.; Bosco, Joseph A.; Slover, James D.; Vigdorchik, Jonathan; Iorio, Richard; Schwarzkopf, Ran
Abstract: Background: Individuals coinfected with both hepatitis C virus (HCV) and HIV represent a unique and growing population of patients undergoing orthopaedic surgical procedures. Data regarding complications for HCV monoinfection or HIV monoinfection are robust, but there are no data available, to our knowledge, on patients who have both HCV and HIV infections. Questions/purposes: We sought to determine whether patients with coinfection differed in terms of baseline demographics and comorbidity burden as compared with patients without coinfection and whether these potential differences were translated into varying levels of postoperative complications, mortality, and hospital readmission risk. Specifically, we asked: (1) Are there demonstrable differences in baseline demographic variables between patients infected with HCV and HIV and those who do not have those infections (age, sex, race, and insurance status)? (2) Do patients with HCV and HIV infection differ from patients without those infections in terms of other medical comorbidities? (3) Do patients with HCV/HIV coinfection have a higher incidence of early postoperative complications and mortality than patients without coinfection? (4) Is the frequency of readmission greater for patients with HCV/HIV coinfection than those without? Methods: The New York Statewide Planning and Research Cooperative System (SPARCS) database was used to identify patients undergoing THA between 2010 and 2014. The SPARCS database is particularly useful because it captures 100% of all New York State inpatient admissions while providing detailed demographic and comorbidity data for a large, heterogeneous patient population with long-term followup. Patients were stratified into four groups based on HCV/HIV status: control patients without disease, HCV monoinfection, HIV monoinfection, and coinfection. We sought to determine whether patients coinfected with HCV and HIV would differ in terms of demographics from patients without those infections and whether patients with HCV and HIV would have a greater risk of complications, longer length of stay, and hospital readmission. A total of 80, 722 patients underwent THA between 2010 and 2014. A total of 98.55% (79, 554 of 80, 722) of patients did not have either HCV or HIV, 0.66% (530 of 80, 722) had HCV monoinfection, 0.66% (534 of 80, 722) HIV monoinfection, and 0.13% (104 of 80, 722) were coinfected with both HCV and HIV. Multivariate analysis was performed controlling for age, sex, insurance, residency status, diagnosis, and comorbidities to allow for an equal comparison between groups. Results: Patients with coinfection were more likely to be younger, male (odds ratio [OR], 2.90; 95% confidence interval [CI], 2.20–3.13; p < 0.001), insured by Medicaid (OR, 6.43; 4.41–7.55; p < 0.001), have a history of avascular necrosis (OR, 8.76; 7.20–9.53; p < 0.001), and to be homeless (OR, 6.95; 5.31–7.28; p < 0.001) as compared with patients without HIV or HCV. Additionally, patients with coinfection had the highest proportion of alcohol abuse, drug abuse, and tobacco use along with a high proportion of psychiatric disorders, including depression. HCV and HIV coinfection were independent risk factors for increased length of stay (OR, 1.97; 95% CI, 1.29–3.01; p < 0.001), having two or more in-hospital complications (OR, 1.64; 1.01–2.67; p < 0.001), and 90-day readmission rates (OR, 2.97; 1.86–4.77; p < 0.001). Conclusions: As the prevalence of HCV and HIV coinfectivity continues to increase, orthopaedic surgeons will encounter a greater number of these patients. Awareness of the demographic and socioeconomic factors leading to increased complications after THA will allow physicians to consider interventions such as in-hospital psychiatric counseling, advanced discharge planning, and coordination with social work and collaboration with HCV/HIV infectious disease specialists to improve patient health status to improve outcomes and reduce costs. Level of Evidence: Level III, therapeutic study.